Contaminated marine sediment stabilization/solidification treatment with cement/lime: leaching behaviour investigation - Todaro, Francesco; De Gisi, Sabino; Notarnicola, Michele (Environmental science and pollution research international, 2020)
Among ex situ remediation technologies, stabilization/solidification (S/S) provides for the addition of a binder to dredged materials in order to chemically immobilise the contaminants and improve mechanical behaviour of sediments. The simplest form of treatment is obtained by the addition of Portland cement or lime (calcium oxide), although other additives such as adsorbents may be added. Nevertheless, the success of the S/S treatment may be affected by the contaminants present or by the salt content in the water. In this study, experimental laboratory investigation was carried out on sediments carefully collected from the Mar Piccolo of Taranto in Southern Italy, contaminated by heavy metals, polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs); the goal was to explore the effectiveness of S/S treatment by using Portland cement/lime as binders, monitoring over time (28 days) the leaching of the different mixtures of treated sediment. It is noted that the Mar Piccolo of Taranto is one of the sites of national interest subject to remediation by the Italian government. Once taken within the first meter under the sea floor by a team of experienced divers, the samples were stored at a controlled temperature, characterised in terms of grain size and physical-chemical characteristics and treated by S/S laboratory tests. The results indicate that the addition of binders increased the pH of the mixtures with a consequent leachability of different metals. The mobility of the metals appeared to be governed also by the curing time. The performance of the mixtures in terms of immobilised metals was influenced by the presence of organic contaminants (e.g. organic matter, PAHs and PCBs). As a lesson, high organic matter and fine-grained particles can negatively affect the effectiveness of the S/S treatment in terms of metal immobilisation.